(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
When hematopoietic cells mutate, the first signs of the problem appear within a month. Symptoms depend on the degree of intoxication of the body, damage to internal organs and other factors. Acute leukemia is accompanied by a number of symptoms. The article discusses this disease and its treatment with folk remedies.